Enhanced charge transport properties of rGO-TiO2 based Schottky diode by tuning graphene content. (2019) - Das, Mrinmay; Datta, Joydeep; Biswas, Animesh; Halder, Soumi; Ray, Partha Pratim
Abstract: Here we report the fabrication of Al/rGO-TiO2 Schottky barrier diodes (SBD) and the effect of graphene content on charge transport properties. The SBDs showed better performance after graphene incorporation and the best result was obtained for 5% rGO. We employed space charge limited current (SCLC) theory to estimate the carrier mobility, carrier concentration and diffusion length. For 5% rGO, we achieved a carrier mobility of 0.065 cm 2 V -1 s -1, which is almost a 15 fold increase on pure TiO2 and the diffusion length improved by 35%. The study demonstrates improved charge transport by tuning rGO content, which can be beneficial for device applications.